Sequential occurrence of small cell and non-small lung cancer in a male patient: Is it a transformation?. Issue 12 (2nd December 2017) - Wahab, Ahsan; Kesari, Kavitha; Chaudhary, Siddique; Khan, Mahin; Khan, Hafiz; Smith, Susan; Boumber, Yanis
ABSTRACT: Lung cancer is one of the leading causes of cancer-related mortality and is categorized into small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC). We present a patient with epidermal growth factor receptor (EGFR)-mutant-NSCLC who developed metastatic SCLC after initial therapy with second-generation EGFR-tyrosine kinase inhibitor, afatinib. A 65-year-old male non-smoker was diagnosed with adenocarcinoma of the right lung, stage IVA (M1a). Due to tumor positivity for EGFR-Exon 19 deletion, the patient was started on oral afatinib, which resulted in a partial response. After ten months of treatment, he presented in the office with abdominal pain, distension, weight loss and jaundice. He had diffuse skeletal and hepatic metastases on PET/CT scan with interval progression of his cancer. Although the recurrence of lung adenocarcinoma was suspected, the patient was diagnosed with SCLC on liver biopsy. He received two cycles of chemotherapy and died due to pneumonia and sepsis.